Analysis of Personal Branding Couple of Prospective Candidates in Bogor City of 2018 - Satrio Fajar Imansyah; Ike Atikah Ratnamulyani; Koesworo Setiawan (Indonesian Journal of Social Research (IJSR), 2020)
Regional Election (Pilkada) has been held since 2005, both at the Provincial and Regency/City levels. Election implementation is regulated based on the principle of direct, general, free, confidential, honest and fair, in attracting the sympathy of the people the candidates develop a campaign model through Personal Branding. This concept emphasizes how prospective leaders can influence the people as voters to be willing to give their voting rights. The purpose of this study was to analyze the Personal Branding of a pair of candidates for the Mayor of Bogor City in 2018. The approach in this study was a qualitative research with descriptive analysis method. The results of the study are the personal branding conducted by each pair of candidates either directly or through the media turned out to have a lot of effects especially for millennial voters, but the candidate pair of Mayor of Bogor who did the most personal branding was only the candidate pair of Bogor Mayor elected, while the other pairs of Bogor mayor candidates still tend to use traditional patterns so that it is natural for the elected candidate pairs to win the hearts of voters.